2004
DOI: 10.1007/s00449-003-0346-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess kinetics in a horizontal rotating tubular bioreactor

Abstract: A horizontal rotating tubular bioreactor (HRTB) is a plug flow bioreactor whose interior is provided with O-ring-shaped partition walls that serve as carriers for microbial biomass. During this investigation, microbial biomass was grown in suspension and on the bioreactor inner surface as a microbial biofilm with average mass that was considerably higher than suspended biomass. The dynamics of bioprocess in HRTB was studied by different combinations of process parameters (bioreactor rotation speed and mean res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The obtained bacterial culture was used for the examination of acetate and ammonium ion degradation in HRTB by different combination of process parameters (dilution rate and bioreactor rotation speed). In previous research it was observed that dilution rate had higher effect on the hydrodynamics and bioprocess efficiency in HRTB compared to the bioreactor rotation speed [20][21][22][23][24][25][26][27][28]. Therefore, for the comparison of the performance of HRTB and CSTR experiments in HRTB conducted at different dilution rates (D = 0.033-0.167 h À1 ) and at constant bioreactor rotation speed (n = 15 min À1 ) were chosen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained bacterial culture was used for the examination of acetate and ammonium ion degradation in HRTB by different combination of process parameters (dilution rate and bioreactor rotation speed). In previous research it was observed that dilution rate had higher effect on the hydrodynamics and bioprocess efficiency in HRTB compared to the bioreactor rotation speed [20][21][22][23][24][25][26][27][28]. Therefore, for the comparison of the performance of HRTB and CSTR experiments in HRTB conducted at different dilution rates (D = 0.033-0.167 h À1 ) and at constant bioreactor rotation speed (n = 15 min À1 ) were chosen.…”
Section: Resultsmentioning
confidence: 99%
“…Before this investigation intensive research on mixing in HRTB was carried out with water as a model system [20][21][22][23][24][25] followed by aerobic and anaerobic bioprocesses with mixed microbial culture [26][27][28]. In this work relatively low dilution rates were selected to mimic the long residence times of bacteria in their natural habitats, such as soil or activated sludge [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work the effect of process parameters (n and F) on the mixed microbial culture biofilm formation in HRTB was studied as a continuation of comprehensive research of mixing [18][19][20] and conduction of model bioprocesses in HRTB [23][24][25][26][27]. This investigation started with mixed microbial culture isolation from surface sediments highly contaminated with heavy metals [39][40][41].…”
Section: Biofilm Formation Studies In Hrtbmentioning
confidence: 99%
“…Experiments with varying bioreactor rotation speed are carried out prior to changes of medium inflow rate, since the latter have exhibited higher effects on the bioprocess dynamics and the biofilm stability [23,24,26,27]. , and Cr 6+ (UVVis spectrophotometrical method by Fries and Getrost) [28].…”
mentioning
confidence: 99%